2019
DOI: 10.1016/j.compositesb.2018.08.104
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion control of raw and modified silica particles in PMMA. Impact on mechanical properties, from experiments to modelling

Abstract: Structure and properties of PMMA/silica composites were characterized by various methods including SEM, TGA, rheology, microscopic level evaluation of nanoreinforcement effect on properties. Static modulus and yield strength of PMMA are enhanced with silica incorporation regardless of their dispersion or functionalization. However, composites ultimate properties are strongly affected by fillers characteristics. As expected, better performances are associated to well-dispersed and functionalized silica. A finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Homogeneity is a critical challenge among the various preparation methods of particle-reinforced nanocomposites since the interaction between nano-filler and matrix is the most urgent factor in controlling the properties of nanocomposites. 30,31 The microstructure of produced nanocomposites is illustrated in Figures 2(a)–(d). The evaluation of the SEM images in different magnifications indicated that there is no crucial agglomeration region, and nanoparticles have been distributed appropriately in the polymeric matrix.
Figure 2.SEM micrographs of fractured surfaces for a) pure PMMA and PMMA nanocomposites containing b) 2 wt% TiO 2 , c) 2 wt% SiO 2 , and d) 1 wt% Al 2 O 3 .
…”
Section: Resultsmentioning
confidence: 99%
“…Homogeneity is a critical challenge among the various preparation methods of particle-reinforced nanocomposites since the interaction between nano-filler and matrix is the most urgent factor in controlling the properties of nanocomposites. 30,31 The microstructure of produced nanocomposites is illustrated in Figures 2(a)–(d). The evaluation of the SEM images in different magnifications indicated that there is no crucial agglomeration region, and nanoparticles have been distributed appropriately in the polymeric matrix.
Figure 2.SEM micrographs of fractured surfaces for a) pure PMMA and PMMA nanocomposites containing b) 2 wt% TiO 2 , c) 2 wt% SiO 2 , and d) 1 wt% Al 2 O 3 .
…”
Section: Resultsmentioning
confidence: 99%
“…Various types of silanes are proven to be very efficient for reducing the surface hydroxyl group content in silica particles [ 27 ]. Siot et al investigated the influence of unmodified and poly(methyl methacrylate) (PMMA)-modified silica on mechanical properties [ 28 ]. They showed that particle dispersion processes and modifications with PMMA have a great influence on yield stress and Young’s modulus.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these composites is becoming increasingly popular in the restoration of teeth, where they replace metal dental amalgams, and the reason for that is they are more aesthetically pleasing, have better mechanical properties and are easy to make [16][17][18][19][20]. Silica is the most common reinforcement in dental composite materials [21][22][23]. Composites containing silica have good compatibility with the tissue, they open a great possibility to be shaped in a defined form and their colour can be adjusted to fit many aesthetic demands.…”
Section: Introductionmentioning
confidence: 99%